Inflammatory bowel diseases and the risk of adverse health outcomes: Umbrella review of meta-analyses of observational studies. Issue 7 (July 2021) - Shen, Xiaoding; Wan, Qianyi; Zhao, Rui; Wu, Yutao; Wang, Yong; Cui, Yaping; Su, Xiangnan; Wu, Xiaoting
Abstract: Background and Aim: Accumulating evidence indicates a plausible association between inflammatory bowel diseases and the risk of adverse health outcomes. However, the conclusions are inconsistent. We aimed to perform an umbrella review of meta-analyses to appraise and grade the evidence of the association between inflammatory bowel diseases and the risk of adverse health outcomes. Methods: Meta-analyses of observational studies that examined the associations between inflammatory bowel disease and the risk of adverse health outcomes in PubMed, EMBASE, and Web of Science were screened. Results: This umbrella review identified 25 meta-analyses, which yielded 123 effect estimates for 60 unique putative health outcomes. Patients with inflammatory bowel diseases had a higher risk of adverse health outcomes, including multiple cancers, cardiovascular disease, adverse pregnancy outcomes, adverse oral outcomes, and other adverse events. Moreover, inflammatory bowel diseases caused greater harm to health based on the presented evidence. However, none of the evidence was classified as "high" quality, only 15% was classified as "moderate, " and 65% of outcomes were rated as "very low." Conclusion: Patients with inflammatory bowel diseases had a higher risk of adverse health outcomes and further studies should be conducted to draw firmer conclusions.